The Effect of Panretinal Photocoagulation on Visual Acuity and Macular Thickness in Proliferative Diabetic Retinopathy - Dr. Amer Jawad Kadhim; Dr.Ali Mohammed Ali Al_Jubouri (Genius Journals, 2023)
To report any changes in central macular thickness (CMT) measured by optical coherence tomography (OCT) and visual acuity (VA) measured by Snellen chart after Pan retinal photocoagulation (PRP) in patients with proliferative diabetic retinopathy (PDR) without macular edema
Keywords: edema; Snellen; retinal; optical